The Relationship Between Self-Compassion and Subjective Well-Being Among Preclinical Students in Jambi Province - Tiara Kinsky Ambarita; Dessy Pramudiani; Ayu Ulivia; Annisa Andriani (GAYAKU PUBLISHER, 2026)
This study aimed to examine the relationship between self-compassion and subjective well-being, which comprises life satisfaction, positive affect, and negative affect, among preclinical medical students in Jambi Province. This study employed a quantitative approach with a correlational design and a cross-sectional survey method. The participants consisted of 98 preclinical medical students from universities offering medical programs in Jambi Province who met the inclusion criteria. Self-compassion was measured using the Skala Welas Diri (SWD), while subjective well-being was measured using the Satisfaction with Life Scale (SWLS) for life satisfaction and the Positive and Negative Affect Schedule (PANAS) for positive affect and negative affect. Data were analyzed using Pearson's correlation. The results indicated that self-compassion was significantly associated with all components of subjective well-being, including life satisfaction (r = 0.432, p < 0.001), positive affect (r = 0.297, p = 0.003), and negative affect (r = -0.446, p < 0.001). Higher levels of self-compassion were associated with greater life satisfaction, higher positive affect, and lower negative affect. These findings suggest that self-compassion is associated with subjective well-being among preclinical medical students in Jambi Province.